Comparison between constant-stress and step-stress accelerated life tests under a cost constraint for progressive type I censoring. Issue 1 (15th January 2021) - Hakamipour, Nooshin
Abstract: In accelerated life testing, the products are tested under high stress conditions and the results are used to draw inferences about the product lifetime under the normal stress condition using a regression model. In this article, optimal k -level constant-stress and step-stress accelerated life tests are compared to the Rayleigh failure data under progressive Type I censoring. The objective is to quantify the advantage of using step-stress testing relative to constant-stress testing. Due to constrained resources in practice, stress durations must be determined carefully at the design stage to run an accelerated life test efficiently. The stress durations directly affect the experimental cost and the estimate precision of the parameters of interest. This article investigates the optimal stress durations based on several ( T/C/D/P/R ) optimality criteria under the constraint that the total experimental cost does not exceed a prespecified budget. In addition, these criteria are compared together. Under the budget constraint, these two stress loading schemes are compared. Based on the numerical results, the cost constraint reduces cost and time of the test. It is found that the T -optimal design has the lowest cost and time for the unconstrained testing in both stress loading. Finally, a real data set is analyzed for illustrative purposes.